2022
DOI: 10.22376/ijpbs/lpr.2020.10.5.l221-225
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hearing Loss on Quality of Life in Adults

Abstract: The normal sense of hearing is essential in the social, emotional, psychological and communicative fields. It is needed for safety and also for having a more meaningful life. Causes of hearing loss in adults can be genetic or due to immune diseases, infections such as meningitis, mumps, scarlet fever, Meniere's disease, exposure to loud noises, tumors, head injuries or aging (presbycusis). The word "presbycusis" implies a decrease in hearing associated with the phase of degenerative cochlear aging. Presbycusis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…Em um estudo 23 realizado em 2018 os autores observaram que os familiares apresentam dificuldade na aceitação das limitações ocasionadas pela deficiência auditiva no indivíduo, o que compromete as relações no ambiente domiciliar. Além disso, a família muitas vezes alega que o idoso está "lento" ou "perdendo suas habilidades", o que, nem sempre corresponde à realidade 24 . Essa perspectiva dos familiares pode despertar sentimentos negativos no idoso, favorecendo o isolamento social.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em um estudo 23 realizado em 2018 os autores observaram que os familiares apresentam dificuldade na aceitação das limitações ocasionadas pela deficiência auditiva no indivíduo, o que compromete as relações no ambiente domiciliar. Além disso, a família muitas vezes alega que o idoso está "lento" ou "perdendo suas habilidades", o que, nem sempre corresponde à realidade 24 . Essa perspectiva dos familiares pode despertar sentimentos negativos no idoso, favorecendo o isolamento social.…”
Section: Discussionunclassified
“…Essa perspectiva dos familiares pode despertar sentimentos negativos no idoso, favorecendo o isolamento social. Um estudo 24 realizado em 2010 evidenciou nos relatos de indivíduos com deficiência auditiva adquirida, que o relacionamento familiar ficou prejudicado frente ao déficit sensorial apresentado.…”
Section: Discussionunclassified
“…Several studies have shown stereotyped and prejudiced behaviors of society towards both male and female individuals with hearing impairment. Jha and Singh (2020) has highlighted that even today, society stigmatized hearing-impaired people and considers them weak in establishing social interaction. Today, hearing-loss-induced stigma is common in most underdeveloped and even in modern societies.…”
Section: Introductionmentioning
confidence: 99%